LISTENING ABILITY IN ENGLISH HOMOPHONE AT ENGLISH STUDY PROGRAM MUHAMMADIYAH UNIVERSITY OF BENGKULU - Solehan; Saputra, Eki (CV. Mitkom Indotama, 2024)
This research was aimed to describe the students’ ability in listening English homophone at the fourth semester students of English Study Program of Muhammadiyah University of Bengkulu . The objective of this research is to know listening ability in English homophones by the fourth semester students of English Study Program of Muhammadiyah University of Bengkulu. The design of this research was descriptive quantitative method. The population of this research were fourth semester students. In collecting the data, the researcher did some steps; firstly the researcher distributed questions to students about test homophone. Secondly, the students listen the audio to answer questions. In analyzing the data, the researcher analyzed the data by checking English homophone in the students’ test. Then, the researcher used the formula according to Herzberg and classification according to Arikunto in calculating the percentages of students’ ability in each listening test. The last, the researcher discussed and concluded the data. The result of this research indicated that the students’ ability is good. It can be seen after calculation by using the formula where the classification of test I is “Medium” with average 60% and the classification of test II is “High” with average 70%. So, it can be concluded that listening ability of the students in English Homophone was ‘good’ ability.